Pauperism, Moral Character, and the Liberal State - Valverde, Mariana (Labour / Le Travail, 1992)
The article reviews the books "The Constitution of Poverty: Toward a Genealogy of Liberal Governance," by Mitchell Dean, "Un nouvel ordre des choses: la pauvreté, le crime, l'État au Québec, de la fin du XVIIIe siècle à 1840," by Jean-Marie Fecteau, "Poverty and Compassion: The Moral Imagination of the Late Victorians," by Gertrude Himmelfarb.
Keywords: BOOKS -- Reviews; CONSTITUTION of Poverty: Toward a Genealogy of Liberal Governance, The (Book); DEAN, Mitchell; FECTEAU, Jean-Marie, 1949-2012; HIMMELFARB, Gertrude; Nonfiction; POVERTY & Compassion: The Moral Imagination of the Late Victorians (Book); UN nouvel ordre des choses: la pauvrete, le crime. l' Etat au Quebec, de la fin du XVIIIe siecle a 1840 (Book)